Aeroelastic analysis of a lightweight topology-optimized sandwich panel - Najafi, Maliheh (2023)
Sandwich structures with lattice cores are novel, lightweight composite structures and are widely used in the aerospace industry. Besides, the aeroelastic behavior of sandwich panels in a supersonic flow regime still needs to be thoroughly studied. This work is devoted to investigating the flutter properties of a sandwich panel whose core is inspired by the topology optimization method in supersonic airflow. In addition, an analytical model of the topology-optimized core sandwich panel employing layerwise theory and the homogenization approach is given for modal analysis. A three-layer continuum is applied to the entire sandwich panel, with the topology-optimized core being homogenized as an equivalent orthotropic layer based on an energy method. The first-order shear deformation theory in each layer is assumed, and displacement continuity is imposed at the layer interfaces. These assumptions constitute the foundation of the layerwise theory provided in this study. The supersonic Piston theory evaluates aerodynamic pressure. For the panel, a four-node Lagrangian quadrilateral element with nine degrees of freedom per node is employed. By comparing natural frequencies and mode shapes with those produced from commercial software and previous results in the literature, the accuracy and dependability of the new method are confirmed. On critical dynamic pressure, the effects of geometric parameters and material characteristics are explored. The results show that the proposed metastructure has the ability to use as a lightweight core sandwich panel in comparison to an isotropic panel and isotropic core sandwich panel in aircraft design, which leads to improving the efficiency of flight and is useful in the research of lightweight sandwich materials.